2006
DOI: 10.1016/j.seizure.2006.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-wake habits and disorders in a series of 100 adult epilepsy patients—A prospective study

Abstract: The aim of the study was to assess sleep-wake habits and disorders and excessive daytime sleepiness (EDS) in an unselected outpatient epilepsy population. Sleep-wake habits and presence of sleep disorders were assessed by means of a clinical interview and a standard questionnaire in 100 consecutive patients with epilepsy and 90 controls. The questionnaire includes three validated instruments: the Epworth Sleepiness Scale (ESS) for EDS, SA-SDQ for sleep apnea (SA), and the Ullanlinna Narcolepsy Scale (UNS) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
90
6
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 33 publications
(73 reference statements)
9
90
6
7
Order By: Relevance
“…30,31 Khatami and colleagues examined 100 clinic patients with epilepsy and found sleep onset insomnia in 33 of 98 subjects (34%) and sleep maintenance insomnia in 50 of 97 subjects (52%). 17 Lower prevalence of insomnia in epilepsy patients has been reported by Piperidou and colleagues, who found that only 24% of their cohort of 122 subjects suffered from insomnia, as measured with the Athens Insomnia Scale (AIS). 32 We may relate this discrepancy to different assessment instruments.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…30,31 Khatami and colleagues examined 100 clinic patients with epilepsy and found sleep onset insomnia in 33 of 98 subjects (34%) and sleep maintenance insomnia in 50 of 97 subjects (52%). 17 Lower prevalence of insomnia in epilepsy patients has been reported by Piperidou and colleagues, who found that only 24% of their cohort of 122 subjects suffered from insomnia, as measured with the Athens Insomnia Scale (AIS). 32 We may relate this discrepancy to different assessment instruments.…”
Section: Discussionmentioning
confidence: 95%
“…(8)(9)(10)(11)(12)(13)(14) 51 (33%) Clinical insomnia (moderate severity) (15)(16)(17)(18)(19)(20)(21) 63 (41%) Clinical insomnia (severe) (22)(23)(24)(25)(26)(27)(28) 15 (10%) Most patients were found to have low depressive scores, and this may be secondary to partial and/or successful treatment. Depression represents one of the most common comorbidities of epilepsy and has profound negative impact on the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disorders are 2 to 3 times more common in adults [11][12][13][14] and children 1-10 with epilepsy compared with the general age-matched population, especially when their seizures are poorly controlled or complicated by comorbid neurologic conditions.…”
Section: Questionnaire-based Studies Of the Prevalence Of Primary Slementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] AWE and sleep complaints have significantly lower quality of life than those without sleep problems. [11][12][13]15,16 Sleep problems in children and adolescents with epilepsy are associated with negative effects on daytime behavior and academic performance. [17][18][19] Recognition of this situation has led to more patients referred to sleep centers to evaluate whether untreated sleep disorders may be contributing to their seizures.…”
mentioning
confidence: 97%